UJI SOMATIK INKOMPATIBILITAS Ganoderma philippii UNTUK MENGETAHUI POLA SEBARAN PENYAKIT BUSUK AKAR PADA TANAMAN Acacia mangium - Desy Puspitasari; Anto Rimbawanto (Center for Forest Biotechnology and Tree Improvement (CFBTI), 2010)
Ganoderma philipii is a fungi causing root rot disease that have spread widely in Acacia mangium plantation. Study on mode of disease spreading is necessary to develop ways of controlling the spread of the disease. Somatic incompatibility test was carried out using fungal cultures that has been identified as G. philippii from two sites of different rotation. Each location showing different type of incompatibility. Compatible reaction was observed at Logas of first rotation indicating that the isolates are not genotypically distinct and may come from closely related clones. At this site the spread of root rot occurred by root to root contact. Incompatible reaction was observed at Deras of second rotation indicating that G. philipii isolate are genotypically distinct individuals and of different clones, eventhough they share same morphological characters. Genetic diversity found in G. philippii suggested that sexual reproduction of basidiocarps in an important factor and is strongly implicated as one of the main modes of dispersal as well as root to root contact.